RANCANG BANGUN APLIKASI REKOMENDASI NEGARA TUJUAN EKSPOR KOMODITAS UNGGULAN INDONESIA BERBASIS WEB DENGAN METODE TOPSIS - Fahrur, Riska; Pandu Kusuma, Abdi; Dwi Puspitasari, Wahyu (Institut Teknologi Nasional Malang, 2022)
Export is one of the international trade activities carried out by Indonesia, Indonesia's leading export commodities according to data from the Ministry of Trade are from the coffee, cocoa and rubber plantation sectors. This study aims to design and build an application that makes it easier for export players to determine the destination country for marketing products to be exported, especially coffee, cocoa, and rubber by applying the Technique of Order Preference by Similarity (TOPSIS) method. The source of this research data was collected based on export sample documents from 2018 – 2021 produced by the Central Statistics Agency (BPS). In this study, three criteria were used in the TOPSIS calculation, namely transactions, weight (net), and the frequency of imports from the destination country from Indonesia. The results of this research will be used by exporters (users) by looking at the data that has been calculated and sorted. The data with the highest value after being sorted will become a recommendation for the destination country to market products from exporters.